A socio-ecological approach to inclusive physical education in China: A systematic review - Xiao Liang; Minghui Li; Yandan Wu; Xueping Wu; Xiaohui Hou; Cindy Hui-Ping Sit (Frontiers Media S.A., 2022)
BackgroundSince the implementation of inclusive education in China, students with special education needs (SEN) have increasingly been integrating into mainstream schools, like physical education classes. However, inclusive physical education (IPE) in China has developed slowly, and gaps can be found in the knowledge of the factors that inhibit or promote the participation in IPE of students with SEN.ObjectivesThe purpose of this systematic review was to provide a comprehensive summary of the factors related to inclusion in IPE of students with SEN, by applying a socio-ecological model (SEM). Five databases were searched: ERIC, SPORTDiscus with Full Text, Education Full Text (H.W.Wilson), PsychINFO and CNKI in March 2022, to find studies that identify factors regarding IPE in China. Two researchers independently screened studies and summarized relevant data.ResultsFourteen studies were included in the detailed review. By applying the SEM, multi-level factors were identified, ranging from intrapersonal to societal levels that positively or negatively influenced IPE participation in students with SEN. This review indicates that multi-level factors affect the IPE participation of students with SEN in China.ConclusionThe findings will help assist educators and policymakers to develop effective IPE for Chinese students with SEN.